A Brief Telephone Severity Scoring System and Therapeutic Living Centers Solved Acute Hospital-Bed Shortage during the COVID-19 Outbreak in Daegu, Korea - Kim, Shin-Woo (J Korean Med Sci, 2020)
With the epidemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2, the number of infected patients was rapidly increasing in Daegu, Korea. With a maximum of 741 new patients per day in the city as of February 29, 2020, hospital-bed shortage was a great challenge to the local healthcare system. We developed and applied a remote brief severity scoring system, administered by telephone for assigning priority for hospitalization and arranging for facility isolation (“therapeutic living centers”) for the patients starting on February 29, 2020. Fifteen centers were operated for the 3,033 admissions to the COVID-19 therapeutic living centers. Only 81 cases (2.67%) were transferred to hospitals after facility isolation. We think that this brief severity scoring system for COVID-19 worked safely to solve the hospital-bed shortage. Telephone scoring of the severity of disease and therapeutic living centers could be very useful in overcoming the shortage of hospital-beds that occurs during outbreaks of infectious diseases.